Self-Assessment to Improve Speaking Skills in a Private Higher Education Institute - Paredes Morales, Diego Fabricio (2024)
Effective communication skills, particularly in the area of speaking, are indispensable for academic and professional success (Yaseen et al., 2021). However, university students often face significant challenges in developing and demonstrating proficiency in this skill (Andrade, 2009). In this research study, students from a private college institute in Guayaquil found obstacles in producing and interacting during speaking activities, resulting in unsatisfactory performance in final evaluations. One of the primary factors contributing to the difficulties faced by these students is the limited time available for focused speaking practice. Typically, they have only one month of speaking classes within their academic curriculum. Moreover, many of these students lead demanding lives, working in the mornings and attending classes at night. Consequently, they often struggle to allocate sufficient time and energy towards improving their speaking abilities. The evidence of these difficulties are apparent in the students' performance during final evaluations. Despite their strong academic knowledge, their inadequate speaking skills hinder their ability to express themselves, engage in discussions, and convey their understanding of the subject matter. These shortcomings impact their grades, diminish their confidence, and hinder their prospects in future academic and professional activities. Hence, in this research project, it is proposed self-assessment as a strategy to improve students’ speaking skills.